2006
DOI: 10.1348/135910705x43589
|View full text |Cite
|
Sign up to set email alerts
|

His brain is totally different: An analysisof care‐staff explanations of aggressive challenging behaviour and the impactof gendered discourses

Abstract: Results indicate that insecure attachment styles of preoccupied and fearful were associated with increased symptom reporting. Social support and anger mediated the relationship between attachment style and symptom reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Previous research has shown that preoccupied (high anxiety/low avoidance) and fearfully (high anxiety/high avoidance) attached individuals consistently report more subjective distress than either dismissing or secure groups during both attachment specific threat (Maunder et al, 2006; Ditzen et al, 2008) and non-attachment provoking situations (Kidd and Sheffield, 2005). Correspondingly, those who had a fearful or preoccupied attachment style reported significantly greater levels of perceived stress compared to those with a secure attachment style in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that preoccupied (high anxiety/low avoidance) and fearfully (high anxiety/high avoidance) attached individuals consistently report more subjective distress than either dismissing or secure groups during both attachment specific threat (Maunder et al, 2006; Ditzen et al, 2008) and non-attachment provoking situations (Kidd and Sheffield, 2005). Correspondingly, those who had a fearful or preoccupied attachment style reported significantly greater levels of perceived stress compared to those with a secure attachment style in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus a secure attachment system leads to adaptive use of resources, more rapid resolution of arousal associated with stress, and consequently, lower allostatic load (McEwen & Getz, 2013). Insecure adult attachment representations (dismissing/avoidant and preoccupied/anxious) are hypothesized to lead to less accurate assessments and less flexible and adaptive coping strategies, as well as more prolonged arousal under stressful conditions (Ciechanowski et al, 2003; Crowell et al, 2002; Feeney & Ryan, 1994; Kidd & Sheffield, 2005; Maunder & Hunter, 2001; Maunder & Hunter, 2009). For example, a dismissing/avoidant attachment stance would be associated with poor identification of stressful experiences, including avoiding and/or dismissing cues and symptoms, over-rating or idealizing one’s own well-being, and/or avoiding the use of close others as supports when stressed.…”
Section: Adult Attachment and Healthmentioning
confidence: 99%
“…While they do make important points, they do not go as far as analysing the gendered effects of these restrictive practices. Although some qualitative projects explore gendered rationales for aggression (Clements, Clare, and Ezelle 1995;Edwards 1999;Hejtmanek 2010;Wilcox, Finlay, and Edmonds 2006), and some studies in mental health units have included women's experiences of restrictive practices, including feelings of retraumatisation (Gallop et al 1999;Jennings 1994;Mohr, Petti, and Mohr 2003), no studies to date have focused solely on analysing experiences of physical restraint from a gender and disability perspective.…”
Section: Gender and Restraint In Institutionsmentioning
confidence: 99%
“…Women service users on Unit C were described as using 'relational aggression' , which was considered to be more difficult to deal with than the type of aggression shown by male service users on the unit (see also Wilcox, Finlay, and Edmonds 2006;Williams, Scott, and Waterhouse 2001). This perceived difficulty legitimated the use of restraint with women, some of whom had been given a Borderline Personality Disorder diagnosis, a distinctly gendered label signifying extreme difficulties with relationships (Becker 1997).…”
Section: Gendered Experiences Of Restraintmentioning
confidence: 99%
See 1 more Smart Citation